Leading Organizational Change: Strategies, Challenges, and the Role of Leadership in Transformation Processes - Baveja, Avriti (Journal of Global Economy, Business and Finance, 2026)
It is evident that leadership plays a defining role in steering organizations through change, whether it involves restructuring, adopting new technologies, or shifting strategic directions. In my view, the ability of leaders to manage resistance, foster commitment, and articulate a compelling vision directly influences the success of transformation efforts. This article delves into various leadership styles—transformational, transactional, situational, and adaptive—analyzing their effectiveness in different change scenarios. It also highlights real - world case studies, such as Steve Jobs at Apple and Jack Welch at General Electric, to illustrate how leadership approaches can drive or hinder organizational progress. Beyond leadership strategies, this discussion underscores key challenges such as cultural resistance, leadership fatigue, and resource constraints. This suggests that successful change management hinges not only on visionary leadership but also on emotional intelligence, clear communication, and an adaptable mindset. Ultimately, organizations that cultivate strong leadership can navigate disruption more effectively, ensuring both survival and long - term growth.